2017
DOI: 10.1002/ab.21697
|View full text |Cite
|
Sign up to set email alerts
|

Generalized hostile interpretation bias regarding facial expressions: Characteristic of pathological aggressive behavior

Abstract: Individuals with aggression regulation disorders tend to attribute hostility to others in socially ambiguous situations. Previous research suggests that this "hostile attribution bias" is a powerful cause of aggression. Facial expressions form important cues in the appreciation of others' intentions. Furthermore, accurate processing of facial expressions is fundamental to normal socialization. However, research on interpretation biases in facial affect is limited. It is asserted that a hostile interpretation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 64 publications
(76 reference statements)
5
50
4
Order By: Relevance
“…The age ranged from 18 to 63 years ( M = 28.52, SD = 10.82). Details with regard to the recruitment of participants from forensic settings are described elsewhere (Brugman et al, ; Cornet, van der Laan, Nijman, Tollenaar & de Kogel, ; Smeijers, Rinck, Bulten, van den Heuvel, & Verkes, submitted). All non‐forensic participants were recruited at Maastricht University using flyers, posters, and a student‐participation system.…”
Section: Methodsmentioning
confidence: 99%
“…The age ranged from 18 to 63 years ( M = 28.52, SD = 10.82). Details with regard to the recruitment of participants from forensic settings are described elsewhere (Brugman et al, ; Cornet, van der Laan, Nijman, Tollenaar & de Kogel, ; Smeijers, Rinck, Bulten, van den Heuvel, & Verkes, submitted). All non‐forensic participants were recruited at Maastricht University using flyers, posters, and a student‐participation system.…”
Section: Methodsmentioning
confidence: 99%
“…In line with this formulation, direct electrophysiological recordings showed that quick amygdala responses to videos depicting interpersonal harm predict intentionality attribution (Hesse et al, 2016). Similarly, individuals with a diagnosis of borderline personality disorder (BPD), who have a tendency to interpret ambiguous faces as hostile (Smeijers, Rinck, Bulten, van den Heuvel, & Verkes, 2017), were faster to direct their gaze toward the eyes of angry-looking faces as a function of amygdala activation (Bertsch et al, 2013). The present results conversely imply that the use of distraction strategies in the presence of threat or provocation might help in curbing aggressive impulses (Lievaart, Huijding, van der Veen, Hovens, & Franken, 2017;Vasquez et al, 2013).…”
Section: Attentional Biases To Antisocial Information and Neurobiolmentioning
confidence: 57%
“…Supporting this interpretation, persons with intermittent explosive disorder (IED) showed enhanced amygdala reactivity to angry faces during both implicit (Coccaro et al, 2007) and explicit emotion processing tasks (McCloskey et al, 2016). Similarly, individuals with a diagnosis of borderline personality disorder (BPD), who have a tendency to interpret ambiguous faces as hostile (Smeijers, Rinck, Bulten, van den Heuvel, & Verkes, 2017), were faster to direct their gaze toward the eyes of angry-looking faces as a function of amygdala activation (Bertsch et al, 2013). Subjects who show stronger interference caused by antisocial cues might thus be more likely to ruminate on the opponent's anger displays and/or to perceive them as more intense.…”
Section: Attentional Biases To Antisocial Information and Neurobiolmentioning
confidence: 97%
“…In addition, it may be argued that such ambiguous or neutral facial expressions may be more common in social interactions in daily life [ 11 ], making this research particularly relevant. To date, few studies have shown that the hostile interpretation bias in people with aggressive tendencies manifests itself indeed in the basic level of facial emotion perception [ 10 , 12 14 ]. For example, Schönenberg and Jusyte [ 10 ] found that violent offenders rated morphed ambiguous faces on an happy-angry or fearful-angry dimension as more angry than healthy volunteers, while no clear differences between groups were present on the more extreme exemplars (e.g., non-ambiguous) of these continua [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This biased perception appeared to be restricted only to emotional dimensions with a component of anger. However, in a recent study among forensic outpatients from Smeijers, Rinck, Bulten, Van den Heuvel and Verkes [ 12 ] a highly generalized hostile interpretation bias was manifested in perception of emotionally ambiguous faces with respect to multiple emotions (not only anger, but also disgust and fear). Moreover, this study showed that this bias appeared to be characteristic of pathological aggression, regardless of intelligence or a psychiatric diagnosis of antisocial or borderline personality disorder or intermittent explosive disorder.…”
Section: Introductionmentioning
confidence: 99%